Evaluation of Scientific Evidence by International Courts and Tribunals in the Continental Shelf Delimitation Cases. (3rd April 2017) - Liao, Xuexia
ABSTRACT: Evaluation of scientific evidence is one of the challenges arising in the tribunal and court cases that deal with the continental shelf beyond 200 nautical miles (nm). Given the difficulties rooted in the interface between law and science regarding the establishment of the entitlement to the continental shelf beyond 200 nm, the current judicial practice offers limited guidance in enhancing transparency and openness in evaluating the scientific evidence. Utilizing procedures providing for the assistance of experts is advisable, as this could facilitate the achievement of an equitable solution in the cases.